The Arterial Vascularization of the Small and Large Intestine in Adult Male Turkeys (Meleagris gallopavo) - Naser, Rabab; Khaleel, Iman M. (The Iraqi Journal of Veterinary Medicine, 2020)
The aim of this study was to reveal the blood supply of the intestinal tract in male adult turkey. Five healthy birds were collected from local suppliers at Baaqoba province. All birds were euthanized and their coelomic cavity was dissected. The descending aorta was cannulated and injected with colored latex, and then the course of arteries along the intestinal tract investigated. Small intestine received the blood by celiac artery, cranial and caudal mesenteric artery. Celiac was split into two branches right and left, the right branch of celiac artery supplied the proventriculus, gizzard, duodenum, pancreas, jejunum and distal part of ileum and cecum while left branch supply the stomach. The crania mesenteric artery nourished the terminal parts of duodenum, jejunum ileum and cranial part of the two ceca, on the other hand. Caudal mesenteric artery was the third artery that supplied the intestine which was short branch originated from descending aorta and divided into two groups cranial groups supplied distal part of ileum and base of ceca while the caudal groups supplied the rectum and cloaca and anastomosed with cranial mesenteric artery. Form the above results, it was concluded that the small and large intestine are nourished by the three major arteries namely Celiac, Cranial and Caudal mesenteric arteries and its branches.